Action Reduce The Rate Of Tax Evasion Through Planning and Tax Fairness - Andi Arifwangsa Adiningrat; Rustan Rustan; Asrah Puspita Ningsih; Siti Aisyah (Jurnal Riset Perpajakan: Amnesty, 2022)
The purpose of this study is to determine whether planning and tax justice have an effect on Tax Evasion. This type of research is carried out with an applied qualitative approach. Data collection techniques used are library methods, documentation studies, observations, and interviews. The results of this study indicate the payment of tax amounts is not only done with a tax plan but can also be due to taxpayer negligence, for example errors in calculating debt. the tax. Tax evasion can also occur because of the low level of tax justice to taxpayers which causes the attitude of taxpayers to lead to negative things and take tax evasion.